The Knowledgebook everything you need to know to get by in the 21st Century. - Wallechinsky, David 1948- (National Geographic Society, 2007)
A comprehensive, visual reference, enhanced by two thousand photographs and illustrations, provides information on all major fields of knowledge and includes timelines, sidebars, cross-references, and other useful features.